Apoptosis and Cell Cycle Pathway-Focused Genes Expression Analysis in Patients with Different Forms of Thyroid Pathology - Bilous, I.; Pavlovych, L.; Krynytska, I.; Marushchak, M.; Kamyshnyi, A.; Камишний, Олександр Михайлович (My University, 2020)
BACKGROUND: Thyroid hormones are key regulators of essential cellular processes, including proliferation, differentiation, and finally, apoptosis. AIM: The aim of the study was to detect changes in the expression of apoptosis and cell cycle pathway-focused genes in patients with different forms of thyroid pathology. PATIENTS AND METHODS: Thirty-six patients with thyroid pathology were enrolled in the study. We used the pathway-specific real-time PCR array (Neurotrophins and Receptors RT2 Profiler PCR Array, QIAGEN, Germany) to identify and verify apoptosis and cell cycle pathway-focused genes expression in patients with post-operative hypothyroidism, hypothyroidism as a result of autoimmune thyroiditis (AIT) and AIT with elevated serum and antithyroglobulin (anti-TG) and anti-thyroid peroxidase (anti-TPO) antibodies. RESULTS: It was shown that patients with elevated serum anti-TG and anti-TPO antibodies and with hypothyroidism resulting from AIT had a significantly lower expression of FAS, TGFB, TP53, and TGFA, while the expression of CD40 was increased. The mRNA levels of BCL2 and BAX decreased in the patients with elevated serum anti-TG and anti-TPO antibodies and increased in the patients with hypothyroidism, resulting from AIT and post-operative hypothyroidism. The patients with hypothyroidism resulting from AIT and post-operative hypothyroidism had significantly lower expression of HSPB1. NF1 expression did not change in all groups of patients. CONCLUSION: The results of this study demonstrate that AIT and hypothyroidism affect the mRNA-level expression of apoptosis and cell cycle pathway-focused genes in a gene-specific manner and that these changes to gene expression can be responsible for the apoptosis signs and symptoms associated with thyroid pathology.
Keywords: Apoptosis; Cell cycle; mRNA; Autoimmune thyroiditis; Hypothyroidism